Effects of Foliar Application of ZnO Nanoparticles on Lentil Production, Stress Level and Nutritional Seed Quality under Field Conditions - Marek Kolenčík; Dávid Ernst; Matej Komár; Martin Urík; Martin Šebesta; Ľuba Ďurišová; Marek Bujdoš; Ivan Černý; Juraj Chlpík; Martin Juriga; Ramakanth Illa; Yu Qian; et al. (Nanomaterials, 2022)
Nanotechnology offers new opportunities for the development of novel materials and strategies that improve technology and industry. This applies especially to agriculture, and our previous field studies have indicated that zinc oxide nanoparticles provide promising nano-fertilizer dispersion in sustainable agriculture. However, little is known about the precise ZnO-NP effects on legumes. Herein, 1 mg·L−1 ZnO-NP spray was dispersed on lentil plants to establish the direct NP effects on lentil production, seed nutritional quality, and stress response under field conditions. Although ZnO-NP exposure positively affected yield, thousand-seed weight and the number of pods per plant, there was no statistically significant difference in nutrient and anti-nutrient content in treated and untreated plant seeds. In contrast, the lentil water stress level was affected, and the stress response resulted in statistically significant changes in stomatal conductance, crop water stress index, and plant temperature. Foliar application of low ZnO-NP concentrations therefore proved promising in increasing crop production under field conditions, and this confirms ZnO-NP use as a viable strategy for sustainable agriculture.